PARTISIPASI MAHASISWA KULIAH KERJA NYATA TEMATIK WIRA DESA (KKNT-WD) DALAM KEGIATAN MASYARAKAT - Puji Muniarty; Wulandari Wulandari; Nabila Putri Sakinah; Bambang Hermanto; Rifka Annisa (ABDIKARYA: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2021)
Real Work Lecture (KKN) is a community empowerment activity by students as a manifestation of the tridharma activities of higher education. Community service activities aim to enable students to implement science and technology as well as skills in the community so that they can become agents of change and sustainable development. The participation of KKN students in community activities plays an important role in the success of work program activities while at the KKN location. This participation can be demonstrated by being directly involved in several preparations for the 76th Independence Day of the Republic of Indonesia held by the Dodu Village Youth Organization. The Bima College of Economics (STIE) with its vision of "Making the Bima College of Economics (STIE) as an educational institution that prints ready-to-use Human Resources and has an entrepreneurial spirit". The spirit of entrepreneurship is interpreted as working without being ordered so that self-awareness is needed here in carrying out various activities. It is evident that the participation of students from various community activities for KKNT-WD STIE Bima students is very high, it is clearly seen from their direct involvement in measuring and cleaning the volleyball field and mutual cooperation in cleaning the surrounding environment.